Establishing a robust framework for monitoring cash flows in treasury operations under legal regulations in agribusiness - Shakhlo Olimjon kizi Shodmonkulova (BIO Web of Conferences)
The rise of the global agri-financial environment presents both regulatory and operational challenges for agribusiness firms entering diverse international markets and deciding capital allocation priorities – a critical topic in agricultural finance and economic risk management. This study investigates the patterns of cash flow management and aims to contribute to the literature on the “liquidity optimization” problem. This paper addresses this issue with empirical insights on how internal and external cash flows are used for financial decision-making by different types of agribusiness enterprises at different stages of production cycles and market expansion, in varied regional and institutional settings. It explains how institutional arrangements and organizational structures, rules, regulatory frameworks, and treasury operations interconnect to influence financial resilience using the cross-sectional dataset and method of multivariate regression analysis, the working capital flow concept, and a comparative-causal inference method. Our findings show that due to the particular risk sensitivity of small and medium-sized agribusiness firms, decision-makers do not welcome the uncertainties related to cross-border capital flows, and the benefit of potential returns from external financing is lower than the perceived risk of abandoning domestic liquidity buffers. They reveal that the “stability preference” effect (maintaining a predictable and steady cash flow cycle) plays a role in investment conservatism and aversion to debt financing. In addition, it is believed that these behavioral tendencies may have long-term consequences for optimizing financial performance.